2022
DOI: 10.1002/for.2897
|View full text |Cite
|
Sign up to set email alerts
|

Trading volume and realized volatility forecasting: Evidence from the China stock market

Abstract: The existing contradictory findings on the contribution of trading volume to volatility forecasting prompt us to seek new solutions to test the sequential information arrival hypothesis (SIAH). Departing from other empirical analyses that mainly focus on sophisticated testing methods, this research offers new insights into the volume‐volatility nexus by decomposing and reconstructing the trading activity into short‐run components that typically represent irregular information flow and long‐run components that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(4 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The studies related to the offshore RMB exchange rate and futures market are the following: Li, Hou and Zhang (2022) [19] studied the relationship between exchange rate fluctuation and risk in the futures market, and they concluded that there is a two-way positive volatility spillover effect between the crude oil futures market and offshore exchange rate market, and there is a significant two-way risk spillover between the offshore exchange rate market and international crude oil futures market. More research can be found in the references [20][21][22][23][24][25][26][27][28][29][30][31]. This study mainly examined the correlation between the return of stock index futures and the return of the offshore RMB exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies related to the offshore RMB exchange rate and futures market are the following: Li, Hou and Zhang (2022) [19] studied the relationship between exchange rate fluctuation and risk in the futures market, and they concluded that there is a two-way positive volatility spillover effect between the crude oil futures market and offshore exchange rate market, and there is a significant two-way risk spillover between the offshore exchange rate market and international crude oil futures market. More research can be found in the references [20][21][22][23][24][25][26][27][28][29][30][31]. This study mainly examined the correlation between the return of stock index futures and the return of the offshore RMB exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CEEMDAN, an enhanced algorithm derived from empirical mode decomposition (EMD) and ensemble empirical mode decomposition (EEMD), addresses the limitations of these methods (Liu et al, 2023). In each stage of the EMD decomposition, the CEEMDAN algorithm dynamically adjusts the noise coefficient.…”
Section: Complete Ensemble Empirical Mode Decomposition With Adaptive...mentioning
confidence: 99%
“…Machine learning methods are widely applied in many fields (Liu et al, 2023; Su et al, 2023; Weng et al, 2021), especially the energy consumption literature, as they are capable to deal with critical problems, such as data missing and the optimization of hyperparameters. For example, Ulucak (2021) used bootstrap auto‐regressive distributive lag to verify the relationship between financial development and energy consumption.…”
Section: Empirical Models and Datamentioning
confidence: 99%